Alkali-activated binder as stabilizer in compressed Earth blocks - Ongpeng, Jason Maximino C. (Animo Repository, 2020)
Compressed earth blocks (CEB) has number of advantages: cost and energy efficient, eco-friendly, non-toxic, and fireproof. It is composed of available compressed soil near project site with binders as stabilizers. From literature, adding ordinary Portland cement (OPC) as stabilizer is practiced. However, the use of OPC produces high carbon footprint in its production phase. This paper aims to use Alkali-activated (AA) binder as stabilizer for the CEB to promote sustainable construction. It uses a combination of fly ash (FA) mixed with Sodium Hydroxide (NaOH) to produce the stabilizer. Compressive strength and water absorption using AA binder as stabilizer in CEB are investigated. Total of fifty-two CEBs with dimensions of 295mm x140mm x100mm are made as an alternative to conventional concrete hollow blocks with a minimum value of 2.50MPa compressive strength from the provision of Philippine National Standard (PNS). The AA binder ratio of 5% and 15% produced compressive strength of 0.42MPa and 2.92MPa, respectively. Additionally, AA binder ratio of 10% produced lowest percentages of water absorption at 12.83%. It shows that the use of CEB with AA binders is possible in achieving sustainable construction building materials. © Published under licence by IOP Publishing Ltd.